Ecology of Urban Slums in Algeria: The Case of Skikda City - Touhami, Brahim; Toumi, Riad (Al-Adab Journal, 2019)
The aim of this study is to investigate the ecology of urban slums in the city of Skikda . Although these slums were established since the colonial era , yet their ecological development and conditions continued to be similar. This study showed that the expansion of SKIKDA slums areas followed a clear pattern , that they grew and expand with the growth of expanding of the city. The study also discovered that some ethnic groups and families occupy the city surrounding areas and establish the slums houses , and eventually become a local community characterized by ethnic behavior. The more the city expand, the more informal areas expand according to the logic of the response to the appropriate solutions for each. The slums in the city of Skikda are at least part of the development of the city since the late colonial period and the period of independence over the last 50 years. The results of the study also revealed the great dependence on the construction process in acquiring the field as a dominant strategy on family behavior, characterization of neighborhood relations within the house and the factors driving housing in slums areas fluctuate mainly between the problem of housing and personal reasons, both of which are linked on the basis that the narrowness of the family housing and the high degree of congestion leads to the leave of married children seeking private shelter. The acquisition of the urban area within the city is carried out through pockets that are out of sight and are located within the urban environment of the city. Based on the evidence and field data obtained through basic indicators to understand the reality highlighted by the slums of Skikda city, the study found a constant fact that the slum culture in Skikda is a behavior and practice through forms of tenure and adaptation patterns promoted by social upbringing with the characteristics of the random area. This culture has re-established the ingredients of producing and reproducing urban slums with all their ecological features.